PENERAPAN MODEL PEMBELAJARAN PREDICT, OBSERVE, EXPLAIN (POE) PADA MATERI LARUTAN ELEKTROLIT DAN NON ELEKTROLIT UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS, SIKAP ILMIAH DAN KEMAMPUAN KOGNITIF SISWA - Evi Christina Gultom (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2018)
Abstract. This research was implementation of Predict, Observe, Explain (POE) model to electrolyte and nonelectrolyte material on the tenth of science students in SMA Negeri 4 Banjarmasin. It aimed for knowingthe differences (1) science process skill, (2) scientific attitude and (3) students’ cognitive ability who learns with the POE modelclass and with conventional class either (expository). This research used quasy experiment method with nonequivalent control group design. The sample of the research was X IPA 2 as the experimental class and X IPA 1 as the controllig class. Data collecting technique used tests and observations.Data analysis technique used descriptive and inferential analysis (normality test, homogeneous test and t-test). Finding showed that (1) there was significant differences in science process skill among students in experimental class and controlling class (2) there was significant differerences in scientific attitude among students in experimental class and controlling class (3) there was significant differences in cognitive ability among students in experimental class and controlling class Keywords: predict, observe, explain (POE) model, science process skill, scientific attitude, cognitive ability